Replenishing the Indus Delta through multi-sector transformation - Awais, Muhammad; Vinca, Adriano; Parkinson, Simon; McPherson, Madeleine; Byers, Edwards; Willaarts, Barbara; Muhammad, Abubakr; Riahi, Keywan (Frontiers in Environmental Science, 2022)
The Indus River Basin (IRB) is a severely water-stressed and rapidly developing South Asia home to an estimated 250 million people. An acute deficit of environmental flows (EF) in the basin’s delta negatively impacts geomorphology and surrounding ecosystems. Here, a sub-national model of the IRB’s integrated water-energy-land systems is applied to quantify multi-sector transformations and system costs for enhancing EFs to the Indus Delta. The results show that increasing average outflows from the basin relative to historical policy levels by 2.5 and 5 times would increase sectoral costs for upstream water users between 17- 32 and 68-72 % for low and high ecological potential targets. The enhanced EFs result in more energy for pumping and treating water upstream from the delta and a net increase in irrigation and energy investments. The EF policy costs are minimized by 7-14% through cooperation across countries and 6-9% through the coordinated implementation of water efficiency measures in the irrigation, conveyance, power plant cooling, and water treatment sectors. The results underscore the crucial role of multi-sector, multi-scale collaboration in achieving EF targets in water-stressed river basins for ecosystem adaptation to climate vulnerability, restoration of the delta, and socio-economic benefits in lower IRB.